Co‐administration of deflazacort and doxycycline: a potential pharmacotherapy for Duchenne muscular dystrophy. (July 2015) - Pereira, Juliano Alves; Marques, Maria Julia; Santo Neto, Humberto
Summary The standard therapy used in the treatment of Duchenne muscle dystrophy (DMD) is corticoids, such as deflazacort and prednisone. However, they have limited therapeutic value, and their combination with drugs already in use to treat other human diseases could potentially increase corticoid outcomes in DMD. In the present study, we evaluated whether a combined therapy of the corticoid deflazacort with doxycycline could result in greater improvement in mdx dystrophy than deflazacort alone. Deflazacort alone or deflazacort/doxycycline were administered for 36 days (starting on postnatal day 0) in drinking water. Histopathological, biochemical (creatine kinase), functional (forelimb muscle grip strength and fatigue) parameters and inflammatory markers (MMP‐9, TNF‐α, NF‐kB) were evaluated in biceps brachii and diaphragm muscles of the mdx mice. The combined therapy was superior in improving the dystrophic phenotype compared to monotherapy. The primary results were observed in attenuating muscle fatigue, decreasing muscle total calcium and inflammatory markers and increasing β‐dystroglycan, a main component of the dystrophin‐protein complex. Furthermore, the combined therapy was effective in preventing the loss of body mass observed with deflazacort alone at this very early stage of therapy. The present study offers preclinical data to support further studies with deflazacort/doxycycline combined therapy in DMD clinical trials.